On sublimation - Rivera, Tania (Discurso, 2007)
The paper discusses the psychoanalytical notion of sublimation from the perspective of Freud’s the Unheimliche, which is nothing but a structure of contradictory signification without synthesis. The Unheimlich is responsible, in Lacan’s phrase, for the elevation “of any given object to the dignity a thing (Ding)”. But such a process could also be the occasion for the glancing at the indignity of a thing.